2008
DOI: 10.1007/s10669-007-9155-z
|View full text |Cite
|
Sign up to set email alerts
|

Surveying of aquatic insect diversity of Chandrabhaga river, Garhwal Himalayas

Abstract: Aquatic insect diversity in the Chandrabhaga,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Relationship between the mean density of macro-invertebrates and water temperature was also found to be negatively correlated (r = -0.92, p [ 0.001) in the present study on Abbreviations: DI = diversity index, AT = air temperature, WT = water temperature, WV = water velocity, HMD = hydromedian depth, TU = turbidity, TA = transparency, CO = conductivity, TDS = total dissolved solids, DO = dissolved oxygen, FCO 2 = free carbon dioxide, pH = hydrogen ion concentration, HD = hardness, Alk = alkalinity, Chl = chloride, NO 3 = nitrate, PO4 = phosphate, Na = sodium, K = potassium the Tons river (Table 7). Similar results were also found during the study on the river Chandrabhaga (Sharma et al 2008). Maximum abundance of macro-invertebrates was found during spring season (February-March) in the Tons river, which may be due to increased growth efficiency of insects during this period in addition to hydrological attributes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Relationship between the mean density of macro-invertebrates and water temperature was also found to be negatively correlated (r = -0.92, p [ 0.001) in the present study on Abbreviations: DI = diversity index, AT = air temperature, WT = water temperature, WV = water velocity, HMD = hydromedian depth, TU = turbidity, TA = transparency, CO = conductivity, TDS = total dissolved solids, DO = dissolved oxygen, FCO 2 = free carbon dioxide, pH = hydrogen ion concentration, HD = hardness, Alk = alkalinity, Chl = chloride, NO 3 = nitrate, PO4 = phosphate, Na = sodium, K = potassium the Tons river (Table 7). Similar results were also found during the study on the river Chandrabhaga (Sharma et al 2008). Maximum abundance of macro-invertebrates was found during spring season (February-March) in the Tons river, which may be due to increased growth efficiency of insects during this period in addition to hydrological attributes.…”
Section: Discussionsupporting
confidence: 86%
“…These macro-invertebrates were identified to the possible lowest taxonomic level. The qualitative analyses of macro-invertebrate samples were made with the help of Fraser (1933); Needham and Needham (1962); Hickel (1977); Macan (1974); Disney (1975); Hynes (1977); Elliott and Humpesch (1983); Kumar and Khanna (1984); Elliott et al (1988); Wallace et al (1990); Ward and Whipple (1992); Rao (1933), Biswas et al (1995); Edington and Hilldrew (1995); Mitra (1999); Mitra (2003); Ramkrishna and Mitra (2004); Sharma et al (2004Sharma et al ( , 2008. The density of macro-inveretbrates was calculated from all the five replicates collected from each sampling site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good number of research works is available on aquatic insects in different countries of the world. Important recent contributions are those of Anbalagan et al (2004), Hsu and Yang (2005), Majumder and Gupta (2005), Dinakaran and Anbalagan (2006), Sharma et al (2008), Thani and Phalaraksh (2008), Ohiokhioya et al (2009) and Das and Gupta (2010). Most of the closed water bodies in Chittagong university campus are not managed habitats.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we have found maximum EPT population at upstream sampling sites where the water quality is relatively clean. Sharma et al (2008) studied aquatic insect diversity of Chandrabhaga river, Garhwal Himalayas and reported that density and diversity of aquatic insects decreases with increase in turbidity, water temperature and decrease in dissolved oxygen.…”
Section: Bio-monitoring Of Water Quality Using Benthic Macro-invertebratesmentioning
confidence: 99%